Soil sampling after corrective application in area planted with sugarcane - Prado, Renato de Mello; Fernandes, Francisco Maximino; Roque, Cassiano Garcia (Pesquisa Agropecuaria Brasileira, 2001)
This work aimed to evaluate the effect of two methods of sampling, in an area planted with sugarcane, on the chemical soil properties, after acidity corrective treatments. The first method consisted of soil sampling in 30% of the collection points located at the line and 70% between the line (LE). The second method consisted of soil sampling in 100% of the points located at the position between the line (E), and of the combination of two sources of corrective agents, scoria and limestone, in correction levels of V% to 50, to 75 and to 100, in addition to one control without correction. Soil sampling according to the method LE overrated the potential acidity, while the soil sampling between the line showed a better adjustment of data for the determination of pH, H + Al, Ca, Mg and V% of the soil.